PENGEMBANGAN KURIKULUM PENGKADERAN HIMPUNAN MAHASISWA TEKNOLOGI PENDIDIKAN BERBASIS PENDIDIKAN KARAKTER - Erwin; Arnidah; Farida Febriati (STKIP Subang, 2023)
This research aims to (1) identify cadre needs; (2) measure the level of validity of cadre curriculum products, and (3) determine the practicality of cadre curriculum products. This research uses an R&D (Research and Development) approach by adapting D. K Wheeler's curriculum development model which refers to the 4D development model. This research was carried out at the Faculty of Education (FIP) Makassar State University (UNM). The subjects of this research were 35 students/administrators of HIMATEP FIP UNM with details: 5 students for individual trials and 30 students for large group trials, as well as 1 organizational supervisor. The data analysis method consists of qualitative descriptive analysis and descriptive statistical analysis. The research results show that: needs analysis is at the required level; the curriculum developed is a cadre curriculum based on character education which contains a cadre implementation plan, cadre materials, and cadre evaluation; product feasibility based on content/material validation with good results, media validation with very good results; individual trials with good results, large group trials with very good results, and responses from organizational supervisors were in the very good category. The conclusion from the results of this research is that the level of analysis of the need for a character education-based cadre curriculum is in the required category, the product is in digital form using a flipbook and has been declared valid and practical.